Sailing with solar and planetary radiation pressure - De Iuliis, Alessia; Ciampa, Francesco; Felicetti, Leonard; Ceriotti, Matteo (Elsevier, 2019)
Literature on solar sailing has thus far mostly considered solar radiation pressure (SRP) as the only contribution to sail force. However, considering a sail in a planetary mission scenario, a new contribution can be added. Since the planet itself emits radiation, this generates a radial planetary radiation pressure (PRP) that is also exerted on the sail. Hence, this work studies the combined eﬀects of both SRP and PRP on a sail for two case studies, i.e. Earth and Venus. In proximity of the Earth, the eﬀect of PRP can be signiﬁcant under speciﬁc conditions. Around Venus, instead, PRP is by far the dominating contribution. These combined eﬀects have been studied for single- and double-sided reﬂective coating and including eclipse. Results show potential increase in the net acceleration and a change in the optimal attitude to maximise the acceleration in a given direction. Moreover, an increasing semi-major axis manoeuvre is shown with and without PRP, to quantify the diﬀerence on a real-case scenario.
Keywords: Planetary sail; solar radiation pressure; albedo; black-body radiation